Graphene-metal sulfide composite based gas sensors for environmental sustainability: A review - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Vineet Kumar; Virendra Kumar Yadav; Ashish Patel; Kulvinder Singh (Sensors International)
In this modern era, maintaining a sustainable environment is pivotal and hence, a detailed review on gas sensors for quantification of toxic environmental pollutants is critical. In this paper, an extensive review on advancements in gas sensors developed using graphene-metal sulfide composites is discussed. Although graphene is an intriguing material with high sensitivity for determination of gases at low concentrations, its poor selectivity is a hindrance towards fabrication of high-performance gas sensors. Hence, hybrid nanocomposites prepared by embedding graphene and its derivatives with various metal sulfides including molybdenum sulfide (MoS2), tin sulfide (SnS2), tungsten sulfide (WS2), cadmium sulfide (CdS) etc. were utilized in gas sensor fabrication with enhanced sensing capabilities. Related investigations revealed that gas sensors using graphene-metal sulfide nanohybrids could be effectively used in detection of individual molecules of toxic gas including NOx, NH3, H2S, SO2, HCHO, CO2, CO, CH4, C3H6O and so on at very low concentrations with good sensitivity and selectivity. A comparative evaluation of various performance parameters revealed that toxic gases were determined with a limit of detection and concentration as low as 0.6 ppb and 0.05 ppm respectively, using graphene-metal sulfide based gas sensors. This review reflects the fact that advancements in material synthesis has led to improvement in gas sensing performances as evidenced from the comparatively better performance metrics reported in recently published articles which utilized hybrid nanocomposites as sensing material.